2020
DOI: 10.2147/cmar.s249979
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC00963 Functions as an Oncogene in Bladder Cancer by Regulating the miR-766-3p/MTA1 Axis</p>

Abstract: Long non-coding RNAs have been found to be involved in bladder cancer development. This article studied LINC00963 effects on bladder cancer progression to provide a novel treatment target. Patients and Methods: Totally 56 bladder cancer patients participated in this research. Bladder cancer cells were transfected. Cell counting kit 8 assay and clone formation experiment were used for cell viability and colony formation detection. Cell migration and invasion were determined by Transwell experiment. LINC00963 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…miRNAs are also identified important in the progression of OS by regulating cell proliferation, EMT, and metastasis ( Leichter et al, 2017 ; Fellenberg et al, 2019 ; Luo et al, 2019 ; Zhang K. et al, 2020 ). miR-766-3p, a tumor suppressor microRNA, is reported to down-regulated in several types of tumor, was remarkably correlated with poor clinical outcomes ( Liu et al, 2020 ; Zhou et al, 2020 ). Nevertheless, to date, there has been no detailed investigations into the functions of miR-766-3p, and the underling mechanisms is far from being fully understood in OS.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are also identified important in the progression of OS by regulating cell proliferation, EMT, and metastasis ( Leichter et al, 2017 ; Fellenberg et al, 2019 ; Luo et al, 2019 ; Zhang K. et al, 2020 ). miR-766-3p, a tumor suppressor microRNA, is reported to down-regulated in several types of tumor, was remarkably correlated with poor clinical outcomes ( Liu et al, 2020 ; Zhou et al, 2020 ). Nevertheless, to date, there has been no detailed investigations into the functions of miR-766-3p, and the underling mechanisms is far from being fully understood in OS.…”
Section: Introductionmentioning
confidence: 99%
“…LINC00963 also conferred oncogenic properties in bladder cancer as high LINC00963 expression was observed in bladder cancer patients and indicated high histological grade. Bladder cancer cells viability, colony formation, migration, and invasion can be suppressed by LINC00963 knocking down [ 16 ]. In our study, LINC00963 was found to have a significant high expression level in breast cancer patients in TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00963 has recently been reported to promote breast and hepatocellular carcinogenesis ( 22 , 23 ). Its expression is upregulated in several types of cancer, such as melanoma and bladder cancer ( 24 , 25 ). However, the association between LINC00963 and diabetes has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%